A STUDY OF TWO ARABIC SOURCES OF CLASSICAL RHYME - Hamroyeva Orzigul Jalolovna (European Journal of Humanities and Educational Advancements, 2023)
The article examines two important sources reflecting the theory of classical rhyme: "Mafatih ul-ulum" by Abu Abdullah Khorazmi and "Miftah ululum" by Yusuf Sakkoki.